METAFORA AKTIVITAS MANUSIA DALAM KOSAKATA KEKINIAN BAHASA INDONESIA: KAJIAN SEMANTIK KOGNITIF - Teddy Afriansyah; Millatuz Zakiyah (STKIP Siliwangi, 2022)
For the most part, an understanding of metaphors in the Indonesian vocabulary is lacking when reading from just one point of view. The purpose of this study is, 1) to describe the metaphor of human activity in the Indonesian proverb; 2) to describe the metaphor of human activity in the Indonesian idiom; And 3) todescribe the metaphor of human activity in an Indonesian acronym. The method used in this study is qualitative descriptive. The data-collection techniques used are observation, good libel, and note-taking techniques. The theory used in this study is cognitive semantics. The results of this study are obtained by certain figures in the Indonesian vocabulary classified as metaphorical metaphors based on these types of metaphors that have 17 structural metaphors, 12 ontological metaphors, and 1 orientational metaphors. Based on this data, the most common metaphor is a structural metaphor found in both proverbs, idioms, and acronyms. Whereas the least encountered metaphor is an orientational type. The conclusion is that the metaphor in question has a general sense tendency to describe romance, the troubled life, and the brief response to events summarized on the theme life's dilemma.